126k views
1 vote
Find the property of this : 5x*(4y+3x)=5x*(3+4y)

User Tsap
by
4.9k points

2 Answers

4 votes

Answer:

0

Explanation:

5x • (3x + 4y) - 5x • (4y + 3) =

User Gkpo
by
4.8k points
4 votes
Simplifying
5x(4y + 3x) = 5x(3x + 4y)

Reorder the terms:
5x(3x + 4y) = 5x(3x + 4y)
(3x * 5x + 4y * 5x) = 5x(3x + 4y)

Reorder the terms:
(20xy + 15x2) = 5x(3x + 4y)
(20xy + 15x2) = 5x(3x + 4y)
20xy + 15x2 = (3x * 5x + 4y * 5x)

Reorder the terms:
20xy + 15x2 = (20xy + 15x2)
20xy + 15x2 = (20xy + 15x2)

Add '-20xy' to each side of the equation.
20xy + -20xy + 15x2 = 20xy + -20xy + 15x2

Combine like terms: 20xy + -20xy = 0
0 + 15x2 = 20xy + -20xy + 15x2
15x2 = 20xy + -20xy + 15x2

Combine like terms: 20xy + -20xy = 0
15x2 = 0 + 15x2
15x2 = 15x2

Add '-15x2' to each side of the equation.
15x2 + -15x2 = 15x2 + -15x2

Combine like terms: 15x2 + -15x2 = 0
0 = 15x2 + -15x2

Combine like terms: 15x2 + -15x2 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.
User VDN
by
4.7k points